The concept of virginity from the perspective of Iranian adolescents: a qualitative study - Mohammad Hossein Mehrolhassani; Vahid Yazdi-Feyzabadi; Saeid Mirzaei; Farzaneh Zolala; Ali-Akbar Haghdoost; Nadia Oroomiei (BMC, 2020)
Abstract Background Premarital sex can increase the risk of sexually transmitted diseases (STDs) in adolescents, and lack of premarital sex can be considered as a reliable policy for STD prevention, which is used by some countries such as Iran. Since the success of this policy is related to the concept of virginity, the present study was conducted to determine the concept of virginity from the perspective of Iranian adolescents. Methods In this qualitative study with phenomenological approach, the research team visited public places, including parks and coffee shops, and interviewed a number of 15-19-year-old adolescents. The data were collected using in-depth interviews with semi-structured questions and analysed using thematic analysis method. Results Several themes, including virginity as the lack of emotional relationship with the opposite sex, lack of physical contact, nonpenetrative relationship, virginity as a myth, virginity as a commitment, having an intact hymen, and not knowing the meaning of virginity, were extracted from the data. Conclusion The most reliable policy on STD prevention is the lack of premarital sex. The success of this policy is related to the concept of virginity. The findings of this study showed that the participants did not consider physical contact as the breach of virginity. This may indicate that the policy of not having sex before marriage or lack of premarital sex is not enough and Iranian adolescents are at risk of STDs. Therefore, policymakers must take steps towards modifying the concept of virginity in the adolescents' value system and provide and implement educational programs on sexual health for adolescents.